Cylindrospermopsin impairs tubular transport function in kidney cells LLC-PK1. (15th June 2021) - Moraes, A.C.N.; Freire, D.S.; Habibi, H.; Lowe, J.; Magalhães, V.F.
Highlights: Cylindrospermopsin induces necrosis in tubular cells. Cylindrospermopsin decreases albumin uptake by tubular cells. Cylindrospermopsin changes transcript abundance of proteins involved in endocytosis. Cylindrospermopsin mechanisms of tubular damage. Abstract: Cylindrospermopsin (CYN) has been involved in cases of poisoning in humans following ingestion. Studies have demonstrated that the kidney is the most affected organ. CYN exposure leads to low-molecular-weight proteinuria and increased excretions of the tubular enzymes in mice, suggesting the damage caused by CYN is mainly tubular. However, the mechanism involved in CYN nephrotoxicity remains unknown. Thus, in order to evaluate the effects of CYN exposure (0.1, 0.5 and 1.0 μg/mL) on tubular renal cells LLC-PK1 distinct mechanisms were analyzed by assessing cell death using flow cytometry, albumin uptake by fluorescence analysis, Na + /K + -ATPase activity by a colorimetric method, RT-qPCR of genes related to tubular transport and function as well as internalization of CYN by ELISA. In this study, CYN was found to induce necrosis in all concentrations. CYN also decreased albumin uptake as well as downregulated megalin and dab2 expression, both proteins involved in albumin endocytosis process. Moreover, CYN appears to be internalized by renal tubular cells through a receptor-mediated endocytosis. Finally, the present study demonstrates that CYN is responsible for disrupting tubular cell transport and function in LLC-PK1 cells.